Behavior of hollow steel stub-columns in-filled with green concrete incorporating ground granulated blastfurnace slag (GGBS) - See, Chee Seong. (2011)
As a key segment of our economy, the construction industry plays an important role in providing the infrastructure and buildings to support our economic development. Increasingly, the industry will have to play a greater role in shaping a sustainable environment for Singapore, now and the future. One of the aspects of sustainable construction which the Building and Construction Authorities (BCA) is trying to implement is applying the recycle material in concrete production and civil engineering works.The use of green concrete is one of the important steps towards sustainability development.